Rutaecarpine Inhibits Doxorubicin-Induced Oxidative Stress and Apoptosis by Activating AKT Signaling Pathway - Liao, Zi-Qi; Jiang, Yi-Nong; Su, Zhuo-Lin; Bi, Hai-Lian; Li, Jia-Tian; Li, Cheng-Lin; Yang, Xiao-Lei; Zhang, Ying; Xie, Xin (Frontiers in Cardiovascular Medicine, 2022)
Patients with cancer received doxorubicin (DOX) treatment always comes at a price of cardiac dysfunction and finally developed into heart failure. Oxidative stress is considered as the most important mechanism for DOX mediated cardiotoxicity. Rutaecarpine (Rut), a quinazolinocarboline alkaloid extracted from Evodia rutaecarpa, was shown to have a protective effect on cardiac disease. The purpose of this study is to investigate the role of Rut in DOX-induced cardiotoxicity and explore the underlying mechanism. Intravenous injection of DOX (5 mg/kg, once a week) in mice for 4 weeks was used to establish the cardiotoxic model. Echocardiography and pathological staining analysis were used to detect the changes of structure and function in the heart. The western blot and real-time PCR analysis were used to detect the molecular changes. In this study, we found that DOX time-dependently decreased cardiac function with little systemic side effects. Rut inhibited DOX-induced cardiac fibrosis, reduction of heart size and decrease of the heart function. Moreover, Rut alleviated DOX-induced reduction of superoxide dismutase (SOD) and glutathione (GSH), enhancement of malondialdehyde (MDA). Meanwhile, Rut inhibited DOX-induced apoptosis in the heart. Importantly, we further found that Rut activated AKT/ nuclear factor erythroid 2-related factor 2 (Nrf-2) which further upregulated the antioxidant enzymes such as heme oxygenase-1 (HO-1) and glutathione cysteine ligase modulatory subunit (GCLM) expression. AKT inhibitor partially inhibited Nrf-2, HO-1 and GCLM expression, and abolished the protective role of Rut in DOX-induced cardiotoxicity. In conclusion, this study identified Rut was a potential therapeutic agent for treating DOX-induced cardiotoxicity by activating AKT.